PENGEMBANGAN MEDIA PEMBELAJARAN GEOGRAFI PADA MATERI DINAMIKA ATMOSFER MENGGUNAKAN APLIKASI POWTOON - Ganda, Ruth Ellyana Ganda; Delita, Fitra (Indonesian Journal of Educational Technology, 2023)
The research aimed to develop geography learning media on atmospheric dynamics material using the Powtoon application for 10th grade students at SMA Negeri 4 Medan. The media was developed using the ADDIE model, going through the stages of analysis, design, development, implementation, and evaluation. In the analysis stage, the researchers identified the learning needs, analyzed the curriculum, learner characteristics, and learning objectives. The design stage involved storyboarding the content and designing the visuals, animations, audio, and interactions. Key topics covered were atmospheric pressure, wind formation, humidity, precipitation, and weather disturbances. In the development stage, the learning media was created in Powtoon based on the design. Features like animated charts, voiceover explanations, quizzes, and simulations were added to engage students. The learning media was then validated by material and media experts. Revisions were made based on their feedback to improve content accuracy, visual design, and ease of use. In the implementation stage, the learning media was tested on students to evaluate its practicality and effectiveness. The results showed it was engaging, easy to use, and helped improve student understanding and achievement on atmospheric dynamics. Overall, the ADDIE model provided a systematic process for developing interactive, multimedia.